Strategi Peningkatan Kinerja Usaha Mikro Kecil dan Menengah - Giovanni, Axel; Hartono, Budi; Hirawati, Heni; Sijabat, Yacobo P; Lionora, Clarisa Alfa; Aprilia, Vierda Dwi; Witantri, Galuh; Kurniasari, Erika (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2025)
This study aims to identify the internal and external challenges faced by micro, small, and medium enterprises (MSMEs) in Magelang City and to develop effective strategies for enhancing their overall performance. The sample consists of 215 MSMEs selected through snowball sampling, ensuring a comprehensive representation of the sector. Data analysis utilized the internal-external (IE) matrix and the quantitative strategic planning matrix (QSPM) to generate strategic options. The results demonstrate that the strategic formulation using these matrices produces viable alternatives for MSMEs in Magelang, with a specific focus on a market penetration strategy. Concrete actions to implement this strategy include effective customer management, improving product quality and value, addressing customer complaints promptly, establishing partnerships with customers, and creating integrated distribution channels. By adopting these strategies, MSMEs can significantly enhance their competitive edge and achieve better performance outcomes. This research provides valuable insights for MSMEs seeking to navigate challenges and leverage opportunities in the dynamic business environment of Magelang City. Keywords: MSMEs; Strategy; Performance; IE Matrix; QSPM